Microencapsulation of gentamicin into biodegradable polymer as a novel drug delivery system - Mohamed, Farahidah; Harun Ismail, Ahmad Fahmi; Doolaane, Abd Monem (2011)
Current global treatment for acute and chronic orthopaedic infection using non-biodegradable, antibiotic implant are costly and frequently disabling problem that severely affects the patient’s functional outcome and quality of life. Once infection is established, it requires multiple surgeries, prolonged antibiotic treatment, and long-term complications. It was estimated that the average cost of care for implant removal, 6 weeks of parenteral antibiotics, and re-implantation is approximately USD50,000. Therefore, to mitigate the problems, the study here has come out with an innovative product and a cheaper option i.e. a biodegradable micro-carrier system to deliver the antibiotic gentamicin (treatment gold standard) intended as antibiotic implant. The study employed multiple-emulsion solvent evaporation fabrication method to microencapsulate the drug into biodegradable (PLGA) matrix. The gentamicin was found stable and active post-encapsulation with a prolonged release profile observed for a month.